2019
DOI: 10.3389/fevo.2018.00240
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thrips Omnivory and Their Aggregation Pheromone on Multitrophic Interactions Between Sweet Pepper Plants, Aphids, and Hoverflies

Abstract: In complex food webs, plants are commonly attacked by multiple herbivorous species, affecting the preference and performance of other herbivores and natural enemies. The role of omnivorous insects in ecosystems may be more complex because of the consumption of both plant and animal organisms. However, the effect of omnivorous insects on herbivores and natural enemies, has received little attention so far. The main goal of this study was to investigate whether the dual herbivore interaction between aphids and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Although their presence and abundance seem to indicate a relevant role of this taxon in the context of this Alpine environment, it is difficult to draw any conclusions about the biotic interactions in which they might be involved. Indeed, very few studies have investigated their role in natural ecosystems, but they are well known as economically significant crop pests, and, in this context, it was suggested that their presence on plants can impact the behaviour and performance of other visiting insects [92]. The presence of Coleoptera on A. brevis flowers was very limited and therefore probably accidental in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although their presence and abundance seem to indicate a relevant role of this taxon in the context of this Alpine environment, it is difficult to draw any conclusions about the biotic interactions in which they might be involved. Indeed, very few studies have investigated their role in natural ecosystems, but they are well known as economically significant crop pests, and, in this context, it was suggested that their presence on plants can impact the behaviour and performance of other visiting insects [92]. The presence of Coleoptera on A. brevis flowers was very limited and therefore probably accidental in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-computed tomography (micro-CT), which is based on X-rays, allows visualization of the internal anatomy in situ, without the need to dissect the insect; results have been validated by comparing them with classical destructive methodologies 19,20 and it has been used to study the larval digestive and Malpighian tubules of Oestridae 21 Here, using micro-CT it is presented a detailed study of the entire anatomy of the 3rd larval instar (L3) of Sphaerophoria rueppellii (Wiedemann, 1820), a Palearctic species 1 . The species was virtually unknown until recently, when it became commercially available 22,23 and was included in the list of effective agents used in European biocontrol programs against aphids 24 .Bathia 20 under the name of S. avicauda Zetterstedt,1843 (a synonymy of S. rueppelli) described super cially and gured the third instar larva, the cephalic skeleton, prothoracic spiracle, and posterior respiratory processes, and has recently been published on the micromorphology of eggs, third larval instar, and puparium 14 . However, until this study, nothing was known about the internal anatomy of the larvae of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Aphids also serve as model species for the investigation of fundamental ecological questions, e.g. in the areas of endosymbiosis [2], multitrophic interactions [3], population dynamics [4], or climate change biology [5]. Aphid life cycles are highly diverse, with some species alternating between different host plant species, and many alternating between periods of sexual and asexual reproduction [6].…”
Section: Introductionmentioning
confidence: 99%